2020
DOI: 10.3390/d12090359
|View full text |Cite
|
Sign up to set email alerts
|

Intraguild Predation by the Eagle Owl Determines the Space Use of a Mesopredator Carnivore

Abstract: Top predators shape the communities of sympatric predators by killing and displacing smaller predators. Predation risk pushes smaller predators to select enemy-free spaces irrespective of food availability, which results in changes in their behaviour, space use, distribution, and abundance. Although the landscape of fear dynamics are known for top predators such as the eagle owl and its impact on smaller raptors, the effect of the presence and abundance of the eagle owl on the space use of mesopredator carnivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…Genets and martens are behaviourally and ecologically similar and could be expected to develop analogous strategies to cope with larger predators. However, the stone marten almost disappeared from the Iberian lynx territories, which is in accordance with the strong avoidance patterns found by Monterroso et al 17 and Virgós et al 50 . In contrast, the common genet co-existed spatially with the apex predator in low density by developing fine-scale spatio-temporal mechanisms 18,33 , similarly to observations of Jiménez et al 26 for other mesocarnivores following Iberian lynx reintroduction.…”
Section: Discussionsupporting
confidence: 90%
“…Genets and martens are behaviourally and ecologically similar and could be expected to develop analogous strategies to cope with larger predators. However, the stone marten almost disappeared from the Iberian lynx territories, which is in accordance with the strong avoidance patterns found by Monterroso et al 17 and Virgós et al 50 . In contrast, the common genet co-existed spatially with the apex predator in low density by developing fine-scale spatio-temporal mechanisms 18,33 , similarly to observations of Jiménez et al 26 for other mesocarnivores following Iberian lynx reintroduction.…”
Section: Discussionsupporting
confidence: 90%
“…Hernandez-Santin et al (2016) showed that feral cats frequently used flat, open spinifex sandplain in their Pilbara ranges and northern quolls avoided areas used by cats spatially and temporally. Moving through spinifex sandplain is likely risky for the smaller quoll, due to the increased chance of intraguild predation (Virgós et al 2020). Reducing the predation risk by feral cats through control programs could benefit quolls by enabling them to make greater use of spinifex sandplains and reducing their reliance on fragmented rocky habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Badgers did not seem to show sensitivity to lynx presence, probably due to their larger size and corpulence (Fedriani et al, 1999). The smaller size of martens and foxes relative to the badger could lead them to be easily predated by a bigger competitor (Virgós et al, 2020) which may explain their low abundance in areas with lynx (see Table S2; Burgos et al, unpubl. ).…”
Section: Lynx Differentially Affect Mesocarnivore Visitationmentioning
confidence: 99%
“…old fields ;Fedriani et al, 2020). Moreover, disturbances on the spatial patterns of scat deposition triggered by predation risk could also occur on an intraspecific level as a consequence of behavioural changes (Virgós et al, 2020) and affect seed dispersal delivery contrastingly. For instance, although foxes dispersed fewer seeds in a predation risk scenario, the possibility cannot be ruled out that they move seeds towards safe forest refuges, which could potentially be suitable habitats for seedling establishment of Mediterranean plants (Bustamante et al, 1992).…”
Section: Implications Of Trophic Cascades On Plant Ecologymentioning
confidence: 99%